Anti-insomniac Botanicals and Natural Products: Pre-clinical and Clinical Evidences. Issue 5 (3rd September 2018) - Nandy, Samapika; Bhattacharyya, Raktim; Mukherjee, Anuradha; Pandey, Devendra Kumar; Dey, Abhijit
Abstract: About one third of the world's population is affected by insomnia. Insomnia may be due to various reasons such as physiological, psychological, genetic etc. It affects the health as well as the professional and social life of the affected person. There are many treatment of insomnia, among them pharmacological treatment with benzodiazepine and related tricyclic antihistamines are quite popular. But due to several side effects of these drugs, non-pharmacological and herbal treatments of insomnia are becoming popular day by day. Many types of herbs are reported to have sedative properties in the ethnobotanical evidences around the world. Among them Valerian, Kava Kava, Ginseng, St. John's Wort are most common. Besides these plants there are several other plants which are also used in insomnia treatment. Though there are lot of work to be done on herbal treatment of insomnia due to scarcity of reliable data and lack of proper preclinical (using animal models) and/or clinical evidences.